Preliminary Result: Identification of Landslides using Electrical Resistivity Tomography Case Study Mt. Betung - Erlangga Ibrahim; Hikhmadhan Gultaf; Hendra Saputra; Lea Kristi Agustina; Virgian Rahmanda; Cahli Suhendi; M. R. P. Sudibyo; Reza Rizki (Journal of Science and Applicative Technology, 2019)
Institut Teknologi Sumatera (ITERA), ITB and local governments had been cooperated in establishing an astronomy observatory of ITERA Lampung (OAIL), which was located at Mt. Betung in the Pasawaran area. Geological setting of this area showed that the dominant lithology of Mt. Betung is pyroclastic, andesite, and breccia rocks. These volcanic deposits have the potential to move the materials down-slope by the force of gravity, steep slope, and high water-content. We have investigated some area with the potential of a landslide along OAIL construction area, which may be the cause of the landslip as well. We applied electrical resistivity tomography to analyse the electrical properties of the subsurface soil and determine the vulnerable area of the landslide. The result indicated that the area is divided into high resistivity at the top of the soil and low resistivity below. These high resistivity numbers are caused by pyroclastic flow while the lower one is caused by fracture-filled, mostly with water and clay.